2017
DOI: 10.1016/j.oraloncology.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status regulates a novel panel of PIWI-interacting RNAs in head and neck squamous cell carcinoma

Abstract: Objective Smoking remains a primary etiological factor in head and neck squamous cell carcinoma (HNSCC). Given that non-coding RNAs (ncRNAs), including PIWI-interacting RNAs (piRNAs), have emerged as mediators of initiation and progression in head and neck malignancies, we undertook a global study of piRNA expression patterns in smoking-associated HNSCC. Materials and Methods Using RNA-sequencing data from 256 current smoker and lifelong nonsmoker samples in The Cancer Genome Atlas (TCGA), we analyzed the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…In contrast, we found a variety of piRNAs to be expressed in KC from healthy skin. Of 190 piRNAs identified in KC in this study, 33 have previously been described to be expressed in squamous epithelial cells [24] supporting the specificity of our findings. Presently, the significance of piRNA originating outside of transposable elements is largely unknown and piRNAs have already been shown to play a crucial role in host gene regulation [38].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, we found a variety of piRNAs to be expressed in KC from healthy skin. Of 190 piRNAs identified in KC in this study, 33 have previously been described to be expressed in squamous epithelial cells [24] supporting the specificity of our findings. Presently, the significance of piRNA originating outside of transposable elements is largely unknown and piRNAs have already been shown to play a crucial role in host gene regulation [38].…”
Section: Discussionsupporting
confidence: 90%
“…Intriguingly the PIWI-piRNA system has been suggested to regulate essential cellular functions of relevance to the repair of somatic tissues, including cell proliferation, viability, cell invasion and migration [22]. However, most of the newly gained knowledge of the functional role of piRNA is based on cancer studies, including studies on skin cancers [23,24] and oral cancers [25][26][27][28]. It is tempting to hypothesize that piRNAs play a role in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that a collection of 13 piRNAs was found in HNSCC related to smoking. Among those 13 piRNAs, 2 piRNAs are shown to be linked with tumor stage while one piRNA (NON-HSAT067200) is shown to be a potential indicator of patient survival rate [70].…”
Section: Pirnas In Cancermentioning
confidence: 99%